Introduction to Virtual Heritage - Champion, Erik (Bloomsbury Professional, 2015)
The focus of this book—on archaeology and the classics reinvigorated by puppetry and performance, using digital environments—is an interesting and unusual contribution to the area of virtual heritage. In this chapter I wish to quickly cover some of the changes in the development and thinking behind virtual heritage, and to consider potential advantages of using performance and theatrical devices in the staging of virtual heritage.